Balloon dilation for the treatment of male urethral strictures: a systematic review and meta-analysis - Tianyu Cai; Xiaoyu Li; Jian Lin; Chunru Xu; Xing Ji; Zhenpeng Zhu; Zhenke Guo (BMJ Open)
Objective The use of minimally invasive endoluminal treatment for urethral strictures has been a subject for debate for several decades. The aim of this study was to review and discuss the safety, efficacy and factors influencing the clinical application of balloon dilation for the treatment of male urethral strictures.Design Systematic review and meta-analysis.Data sources Embase, Medline, Web of Science, Cochrane Library and Scopus were searched for publications published before 17 July 2022.Study selection Two independent researchers screened and assessed the results, and all clinical studies on balloon dilation for the treatment of urethral strictures in men were included.Data extraction and synthesis The success rate, rate of adverse events, International Prostate Symptom Scores, maximum uroflow (Qmax) and postvoid residual urine volume were the main outcomes. Stata V.14.0 was used for statistical analysis.Results Fifteen studies with 715 patients were ultimately included in this systematic review. The pooled results of eight studies showed that the reported success rate of simple balloon dilation for male urethral strictures was 67.07% (95% confidence interval [CI]: 55.92% to 77.36%). The maximum urinary flow rate at 3 months (risk ratio [RR]= 2.6510, 95% CI: 1.0681 to 4.2338, p<0.01) and the maximum urinary flow rate at 1 year (RR= 1.6637, 95% CI: 1.1837 to 2.1437, p<0.05) were significantly different after dilation. There is insufficient evidence to suggest that balloon dilation is superior to optical internal urethrotomy or direct visual internal urethrotomy (DVIU) (RR= 1.4754, 95% CI: 0.7306 to 2.9793, p=0.278).Conclusion Balloon dilation may be an intermediate step before urethroplasty and is a promising alternative therapy to simple dilation and DVIU. The balloon is a promising drug delivery tool, and paclitaxel drug-coated balloon dilation is effective in reducing retreatment rates in patients with recurrent anterior urethral strictures. The aetiology, location, length, previous treatment of urethral stricture may be associated with the efficacy of balloon dilation.PROSPERO registration number CRD42022334403.